Prevalence, clinical and economic burden of mucormycosis-related hospitalizations in the United States: a retrospective study. Issue 1 (December 2016) - Kontoyiannis, Dimitrios; Yang, Hongbo; Song, Jinlin; Kelkar, Sneha; Yang, Xi; Azie, Nkechi; Harrington, Rachel; Fan, Alan; Lee, Edward; Spalding, James
Abstract Background Mucormycosis is a rare but devastating fungal infection primarily affecting immunocompromised patients such as those with hematological malignancy, bone marrow and solid organ transplantation, and patients with diabetes, and, even more rarely, immunocompetent patients. The objective of this study was to assess the prevalence and burden, both clinical and economic, of mucormycosis among hospitalized patients in the U.S. Methods This is a retrospective study using the Premier PerspectiveTM Comparative Database, with more than 560 participating hospitals covering 104 million patients (January 2005-June 2014). All hospitalizations in the database were evaluated for the presence of mucormycosis using either an ICD-9 code of 117.7 or a positive laboratory result for Mucorales. Hospitalizations were further required to have prescriptions of amphotericin B or posaconazole to be considered as mucormycosis-related hospitalizations. The prevalence of mucormycosis-related hospitalizations among all hospital discharges was estimated. Mortality rate at discharge, length of hospital stay, and readmission rates at 1 and 3 months were evaluated among mucormycosis-related hospitalizations. Cost per hospital stay and average per diem cost (inflated to 2014 USD) were reported. Results The prevalence of mucormycosis-related hospitalizations was estimated as 0.12 per 10, 000 discharges during January 2005-June 2014. It increased to 0.16 per 10, 000 discharges if the definition of mucormycosis was relaxed to not require the use of amphotericin B or posaconazole. The median length of stay was 17 days, with 23% dead at discharge; readmission rates were high, with 30 and 37% of patients readmitted within one and three months of discharge, respectively. The average cost per hospital stay was $112, 419, and the average per diem cost was $4, 096. Conclusions The study provides a recent estimate of the prevalence and burden of mucormycosis among hospitalized patients. The high clinical and economic burden associated with mucormycosis highlights the importance of establishing active surveillance and optimizing prophylactic and active treatment in susceptible patients.